Politics of Autonomy and Sustainability in Myanmar Change for New Hope...New Life? - Tantikanangkul, Walaiporn; Pritchard, Ashley; SpringerLink (Online service) (Singapore : Springer Singapore (Imprint), 2016)
This book focuses on the tensions between and conflict resolution processes concerning minority ethnic groups in Myanmar's rural areas and the State. It covers topics such as relations and communication between the central government, the Kokang Chinese community and the Kachin State; the impact of cyclone Nargis on remote settlements in the Ayeyarwady Delta; the impact of depletion of mangrove forests and Yangon's fuel needs on a Karen minority group; and the collapse of a community forestry project in a Pa-O village in Shan State. Written by young scholars from Myanmar, some of whom belong to minority groups, the book provides firsthand reporting and scholarship that, for the past sixty years, have not been available. Offering in-depth, unique insights into minority change issues in the interior and at the periphery of Myanmar, as seen from local perspectives, it offers a valuable resource for academics, students and researchers in the fields of sustainable development, social and political studies, and development communication in Asia.
Chapter 1: Introduction -- Chapter 2: Kokang - The Rise of the Chinese Minority - The New Neo-Liberal State? -- Chapter 3: Laiza - Kachin Borderlands-Life after the Ceasefire -- Chapter 4: Post-Nargis Lives - After the Storm - Comes the New Hope? -- Chapter 5: Mangroves in Myanmar: Conflicts and Impacts -- Chapter 6: Sustainability in Pa-O Forest: Will There Be Hope for the Locals?.
Keywords: Comparative Politics